The association between structural connectivity and anti‐seizure medication response in patients with temporal lobe epilepsy - Dong Ah Lee; Junghae Ko; Sung‐Tae Kim; Ho‐Joon Lee; Kang Min Park (Epilepsia Open)
Abstract Objectives This study aimed to investigate the differences in structural connectivity and glymphatic system function between patients with temporal lobe epilepsy (TLE) and hippocampal sclerosis (HS) and healthy controls. Additionally, we analyzed the association between structural connectivity, glymphatic system function, and antiseizure medication (ASM) response. Methods We retrospectively enrolled patients with TLE and HS and healthy controls who underwent diffusion tensor imaging at our hospital. We assessed structural connectivity in patients with TLE and HS and healthy controls by calculating network measures using graph theory and evaluated glymphatic system function using the diffusion tensor image analysis along the perivascular space (DTI‐ALPS) index. Patients with TLE and HS were categorized into two groups: ASM poor and good responders. Results We enrolled 55 patients with TLE and HS and 53 healthy controls. Of the 55 patients with TLE and HS, 39 were ASM poor responders, and 16 were ASM good responders. The assortativity coefficient in patients with TLE and HS was higher than that in healthy controls (0.004 vs. −0.007, p = 0.004), and the assortativity coefficient in ASM poor responders was lower than that in ASM good responders (−0.001 vs. −0.197, p = 0.003). The DTI‐ALPS index in patients with TLE and HS was lower than that in healthy controls (1.403 vs. 1.709, p < 0.001); however, the DTI‐ALPS index did not differ between ASM poor and good responders (1.411 vs. 1.385, p = 0.628). The DTI‐ALPS index had a significant negative correlation with age in patients with TLE and HS (r = −0.267, p = 0.049). Significance We confirmed increased assortativity coefficient in structural connectivity and decreased DTI‐ALPS index in patients with TLE and HS compared with healthy controls. Additionally, we demonstrated an association between decreased assortativity coefficient in structural connectivity and ASM poor response in patients with TLE patients and HS. Plain Language Summary This study investigates the relationship between brain connectivity changes and glymphatic system function with antiseizure medication response in patients with temporal lobe epilepsy and hippocampal sclerosis. The research reveals that these patients show altered brain connectivity and glymphatic function compared to healthy individuals. A key finding is the strong link between a specific connectivity measure (assortativity coefficient) and antiseizure medication response, providing valuable insights that could influence epilepsy treatment and future research directions.